ASSOCIATION BETWEEN RESPIRATORY COMPLAINTS AND PM 10 CONCENTRATION IN HOUSEHOLDS IN PALEMBANG - Ameria; Maksuk, Maksuk; Amar Muntaha (Perhimpunan Ahli Epidemiologi Indonesia, 2022)
Background: Acute Respiratory Infections (ARI) cause around 4 million under-five deaths in developing countries, including Indonesia. Air quality is strongly influenced by human activities. Purpose: This study was to analyze the relationship between PM10 concentrations in the house and the risk factors for the health conditions of the household environment and human characteristics on the incidence of respiratory disorders. Methods: This research is an analytic observational with a cross-sectional design. The number of samples calculated as many as 60 respondents were taken randomly. This research was conducted in Pulokerto Village, Gandus District, Palembang from August to December 2009. Data were collected through observation and interviews using a questionnaire, while indoor air samples were measured using the EPAM 5000 instrument by BTKL PP Palembang officers. Data were analyzed by univariate, bivariate using chi-square test, and multivariate using multiple logistic regression. Results: The results of statistical tests showed that the usage of insect repellent (p v = 0.0005, OR = 13.095, 95% CI = 3,821-44,882), smoking habits (p v = 0.0005, OR = 15.536, 95% CI = 3.114-77.519), Indoor PM10 concentration (pv=0.021, OR=3.463, 95% CI (1.186 – 10.108) While the most dominant variable affecting respiratory disorders is the usage of insect repellent. Conclusion: The factors that have the greatest influence in causing respiratory disorders are age, gender, education, population density and the use of mosquito repellent.